Regional assessment of facial nerve paralysis using optical flow method - Wan Syahirah, Wan Samsudin; Rosdiyana, Samad; Kenneth, Sundaraj; Mohd Zaki, Ahmad; Pebrianti, Dwi (Springer, 2019)
This paper presents an ultra-wideband pyramidal horn antenna for non-destructive fruit quality monitoring system. The proposed design simulation operates in the frequency range of 3.1–10.6 GHz. The antenna is supported by the rectangular waveguide feeder. The design is chosen based on the ability of the antenna to transmit and receive signal with wide bandwidth, high directivity and gain, and low Voltage Standing Wave Ratio. The antenna is designed and simulated by using Computer Simulation Technology Microwave Studio. The simulation result also validated by the experimental result. The simulation result shows that the proposed UWB pyramidal horn antenna exhibits small return loss with low VSWR as well as good radiation pattern in the frequency range of 3.1–10.6 GHz.